On the Systematic Role of the Deduction of Categories in “The Logical Foundations of the Exact Sciences” - Laura Pelegrin (RUDN Journal of Philosophy)
This work studies the systematic role of the deduction of categories in Paul Natorp’s Logical Foundations of the Exact Sciences. Through an analysis of the deduction of the categories of quantity and quality, we contend that this deduction is not merely a historiographical exercise, but it is the core of Natorp’s system. It is argued that Natorp follows a synthetic method, rather than an analytic, similar to that employed by Kant in the Critique of Pure Reason . We argue that the core of Natorp’s deduction is rooted in the principle of correlation. Unlike Kant, who derives categories from the table of judgments, Natorp constructs his deduction by examining the structure of thought itself. We demonstrate that this approach allows for a systematic deduction of the properties of number and the fundamental series. The study shows how this deduction of categories is the ground for the construction of the fundamental series and how it is aligned with Natorp’s methodological prescriptions.